Optimal bond trading and the tax-timing option in Canada - Prisman, Eliezer Z.; Roberts, Gordon S.; Tian, Yisong (Journal of Banking & Finance, 1996)
The goal of this paper is to determine whether the tax-timing option effect documented in the U.S. bond market exists outside the U.S. Examining Canadian tax rules suggests that the tax option effect is simpler and less valuable than in the U.S. This view is supported by simulations in the spirit of Constantinides and Ingersoll (1984) as well as by empirical tests conducted on bond triplets following Jordan and Jordan (1991).